Psycholocial factors affecting disabled Paralympians and the management controlling strategies - Zhang, X.; Zheng, W.; Qi, C. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: In fierce competitive sports, the level of the competitive state directly impacts on the competitive strength achieved. The psychological factor is particularly important in order to compete at a high level and achieve the best competitive state. This study investigated the impact of psychological factors on the Chinese windsurfing team during their preparation for the 2008 Beijing Paralympics. The paper also discusses the control strategy used to manage these factors. Methods A comprehensive review of the literature was conducted as well as interviews and topological analysis. Results The data from interviews and surveys indicated that some of the psychological factors include the stability of a player`s psychological state, goal orientation, self-efficacy, and notice focus. Further factors include clarity of focus, a strong sense of self-efficacy and psychological stability. These characteristics of Chinese disabled athletes will help them to achieve the best competitive state. With regard to the competitive state of psychological factors on yachting athletes, the control strategy was a psycholoical state of stability and encouragement of the athletes to take part in more competitions. The accumulation of experience on the psychological state of stability was especially important to establish solid game goal stereotypes and turn this into strong internal emotional as well as achieve ultimate synchronization. In order to enhance individual self-efficacy, confidence, and a belief that one can overcome any difficulties and promote the best competitive state formation the players` attention level needed to be higher than normal. Psychological training can help focus on the immediate tasks and form a clear focus. In addition, recall of the memories of successful game experience can strengthen the motives for competition and enhance the competition state. Conclusions Based on the results, the study concluded that a clear focus, strong sense of self-efficacy and psychological stability would impact on Chinese disabled athletes and help them to achieve the best competitive state. This finding may also help athletes take part in more competitions and establish well developed competitive goals.